Improving mortality of coronary surgery over first four years of independent practice: retrospective examination of prospectively collected data from 15 surgeons. Issue 7463 (6th August 2004) - Bridgewater, Ben; Grayson, Antony D; Au, John; Hassan, Ragheb; Dihmis, Walid C; Munsch, Chris; Waterworth, Paul
Abstract: Objective To study the "learning curve" associated with independent practice in coronary artery surgery. Design Retrospective analysis of prospectively collected data. Setting All NHS centres in north west England that carry out cardiac surgery in adults. Participants 18 913 patients undergoing coronary artery surgery for the first time between April 1997 and March 2003, 5678 of whom were operated on by 15 surgeons in the first four years after their consultant appointment. Main outcome measures Observed and predicted mortality (EuroSCORE) for surgeons in their first, second, third, and fourth years after appointment as a consultant compared with figures for established surgeons. Results Overall mortality decreased over the six years of study (P = 0.01). Of the patients operated on by established surgeons or newly appointed consultants, 265/13 235 (2.0%) and 109/5678 (1.9%), respectively, died (P = 0.71). There was a progressive decrease in observed mortality with time after appointment as a consultant from 2.2% in the first year to 1.2% in the fourth year (P = 0.049). This result remained significant after adjustment for time and case mix (P = 0.019). Conclusions Mortality in patients operated on by newly appointed consultant surgeons is similar to mortality in patients operated on by established surgeons. There are significant decreases in crude and risk adjusted mortality in the four years after appointment. These findings should influence the nature of practice in newly appointed surgeons.